Respuesta :
Given expression is
[tex]10 \frac{3}{7} + 19 \frac{5}{9} [/tex]
Now convert mixed fraction as improper fraction as
[tex]10 \frac{3}{7} + 19 \frac{5}{9} = \frac{10*7 + 3}{7} + \frac{19*9+5}{9} [/tex]
[tex]= \frac{73}{7} + \frac{176}{9} [/tex]
[tex]= \frac{73*9 + 176 * 7}{63} [/tex]
[tex]= \frac{657 + 1232}{63} = \frac{1889}{63} [/tex]
Now we can convert [tex] \frac{1889}{63 } = 29 \frac{62}{63} [/tex]
So the answer is [tex]29 \frac{62}63} [/tex]
[tex]10 \frac{3}{7} + 19 \frac{5}{9} [/tex]
Now convert mixed fraction as improper fraction as
[tex]10 \frac{3}{7} + 19 \frac{5}{9} = \frac{10*7 + 3}{7} + \frac{19*9+5}{9} [/tex]
[tex]= \frac{73}{7} + \frac{176}{9} [/tex]
[tex]= \frac{73*9 + 176 * 7}{63} [/tex]
[tex]= \frac{657 + 1232}{63} = \frac{1889}{63} [/tex]
Now we can convert [tex] \frac{1889}{63 } = 29 \frac{62}{63} [/tex]
So the answer is [tex]29 \frac{62}63} [/tex]